Ongoing intensification of anomalous Western North Pacific anticyclone during post-El Niño summer with achieved carbon neutrality - Wen Zhang; Weichen Tao; Gang Huang; Kaiming Hu; Xia Qu; Ya Wang; Haosu Tang; Suqin Zhang (npj Climate and Atmospheric Science)
Abstract Analysis of a suite of global climate model projections under symmetric CO2 ramp-up and ramp-down (RD) scenarios, our results demonstrate a progressive strengthening of the western North Pacific anticyclone (WNPAC) with rising CO2 concentrations, a trend that persists as CO2 declines, followed by gradual recovery without fully returning to its initial state when CO2 concentrations restore. The overshoot of the WNPAC in the CO2 RD phase is highly correlated with the enhanced anomalous Maritime Continent (MC) convection, which influences WNPAC through reinforced Kelvin wave response or local Hadley circulation adjustment. This enhanced convection is attributed to increased Indo-Pacific zonal SST gradient associated with strengthened MC warming and accelerated decay of El Niño in the Central Pacific, ultimately linked to climatological equatorial Pacific El Niño-like warming pattern-related air-sea processes. The overshoot of the WNPAC during the CO2 RD phase may exacerbate flood and high temperature risks in densely populated East Asia.